Planning for the unexpected in construction projects: a review - Carmo, Cristiano Saad Travassos do; Sotelino, Elisa Dominguez (Brazilian Journal of Production Engineering, 2023)
Global crises, such as pandemic and wars, bring to light how construction projects can be impacted by unexpected events that are typically overlooked by planning teams. Therefore, the goal of this study is to review the literature to understand how uncertainties are being considered in construction planning methods, and what the next steps are to face new crises. By doing so, the authors mapped the traditional variables that are included as uncertainties in planning methods, such as project time and cost, as well as the unusual variables that are not typically included as uncertainties in the methods, such as safety and sustainability issues. The state-of-the-art of planning methods with uncertainties entailed a thorough reading of 103 journal articles found through an adapted systematic literature review, which included, in addition to traditional processes, a scientometric study and a snowballing analysis. As a result, it was discovered that the main uncertainties considered are related to time, cost, and resources. Furthermore, it was possible to observe that there is no single consolidated technique for incorporating uncertainties in planning methods, but rather a combination of different techniques, ranging from the most traditional with analytical analysis to the most contemporary with artificial intelligence algorithms.